Development and Implementation of a Catheter Associated Urinary Tract Infection (CAUTI) 'Toolkit'. Issue 1 (11th September 2015) - Tatham, Mandy; Macfarlane, Gill; MacRae, Morag; Tully, Vicki; Craig, Karen
Abstract: Indwelling urinary catheters are a commonly used invasive medical device within acute and non-acute settings in NHS Scotland. The second National Survey of the Prevalence of Hospital Acquired Infection (HAI) in Scotland 2011 identified that 19.2% of patients surveyed had an indwelling urinary catheter. In this survey, Urinary Tract Infections (UTI) were identified as the most prevalent type of HAI at 22.6% in acute settings and 39% in non-acute settings [1]. In September 2013 the Scottish Government released a Chief Executive Letter (CEL 19) which identified Catheter Associated Urinary Tract Infection (CAUTI) as one of the nine Points of Care Priorities within the Scottish Patient Safety Programme, with the aim of reducing CAUTI by 30% by end of December 2015 measured against a national definition [2]. This quality improvement project saw the development, testing and introduction within NHS Tayside of an evidenced based bundle of care. This was to standardise and drive quality care delivery for the insertion and maintenance of urethral urinary catheters with the intention of reducing catheter associated urinary tract infections in our patients. Data collection tools and data reporting mechanisms were also developed, tested and introduced using a national CAUTI definition to capture data for improvement and local and national reporting of progress.